Fashion in Political Communication - Senaharjanta, Ignasius Liliek; Karmila, Michelle Louise (Future Science, 2024)
Fashion is one aspect of everyday life that plays a role in shaping the identity of an individual or group. This is also true in the political context, where fashion is often used as a feature of political identity and as a means of non-verbal communication. Presidential and vice president candidates along with the campaign team are trying to gain public support in a variety of ways, including through the fashion they wear. The fashion chosen by the presidential and vice president candidates is not just a dress, but also a symbol that contains political meaning, ideology, and a message of communication. Based on that, this research is intended to reveal more deeply about the meaning of the fashion used by the presidential and vice president candidates. The research method used is a descriptive qualitative method with Paul Ricouer's hermeneutic analysis approach. This approach was chosen to dig the meanings hidden in the fashion used by presidential and vice president candidates. The results of fashion research in political communication create new opportunities that can create and generate capital gains for fashion industry entrepreneurs. Thus, fashion in political communication has multiple effects, affecting public perceptions, shaping group identities and creating economic dynamics.